Architectural competitions = architektur Wettbewerbe = Concours d'Architecture / Cees de Jong, Erik Mattie - Jong, Cees De, editor 239095; Mattie, Erik, editor 239101 (Köln, German : Benedikt Taschen, 1994)
Presents a detailed chronological overview of major international architectural competitions in the 19th and 20th centuries - from the White House in Washington to the new Reichstag in Berlin.